LbCas12a mediated suppression of Cotton leaf curl Multan virus - Ashraf, Sidra; Ahmad, Aftab; Khan, Sultan Habibullah; Jamil, Amer; Sadia, Bushra; Brown, Judith K. (Frontiers in Plant Science, 2023)
Begomoviruses are contagious and severely affect commercially important fiber and food crops. Cotton leaf curl Multan virus (CLCuMuV) is one of the most dominant specie of Begomovirus and a major constraint on cotton yield in Pakistan. Currently, the field of plant genome editing is being revolutionized by the CRISPR/Cas system applications such as base editing, prime editing and CRISPR based gene drives. CRISPR/Cas9 system has successfully been used against biotic and abiotic plant stresses with proof-of-concept studies in both model and crop plants. CRISPR/Cas12 and CRISPR/Cas13 have recently been applied in plant sciences for basic and applied research. In this study, we used a novel approach, multiplexed crRNA-based Cas12a toolbox to target the different ORFs of the CLCuMuV genome at multiple sites simultaneously. This method successfully eliminated the symptoms of CLCuMuV in Nicotiana benthamiana and Nicotiana tabacum. Three individual crRNAs were designed from the CLCuMuV genome, targeting the specific sites of four different ORFs (C1, V1 and overlapping region of C2 and C3). The Cas12a-based construct Cas12a-MV was designed through Golden Gate three-way cloning for precise editing of CLCuMuV genome. Cas12a-MV construct was confirmed through whole genome sequencing using the primers Ubi-intron-F1 and M13-R1. Transient assays were performed in 4 weeks old Nicotiana benthamiana plants, through the agroinfiltration method. Sanger sequencing indicated that the Cas12a-MV constructs made a considerable mutations at the target sites of the viral genome. In addition, TIDE analysis of Sanger sequencing results showed the editing efficiency of crRNA1 (21.7%), crRNA2 (24.9%) and crRNA3 (55.6%). Furthermore, the Cas12a-MV construct was stably transformed into Nicotiana tabacum through the leaf disc method to evaluate the potential of transgenic plants against CLCuMuV. For transgene analysis, the DNA of transgenic plants of Nicotiana tabacum was subjected to PCR to amplify Cas12a genes with specific primers. Infectious clones were agro-inoculated in transgenic and non-transgenic plants (control) for the infectivity assay. The transgenic plants containing Cas12a-MV showed rare symptoms and remained healthy compared to control plants with severe symptoms. The transgenic plants containing Cas12a-MV showed a significant reduction in virus accumulation (0.05) as compared to control plants (1.0).